Ekonomi Kreatif: Pemahaman Lingkungan Pemasaran Bagi Siswa Siswi SMA Negeri 3 Sampang - Fuji Santoso; Faisol Faisol (FKIP, Universitas Palangka Raya, 2024)
This community service activity focuses on increasing the understanding of SMA Negeri 3 Sampang students regarding the marketing environment in the context of the creative economy. The creative economy, as a sector that is increasingly developing and important in the global economy. This program is designed to provide students with in-depth insight into marketing concepts and their applications in the creative economy through various educational activities. This community service method involves seminars and interactive discussions that cover materials such as market analysis, marketing strategies, and case studies in the creative industry. This activity is expected to help students understand how to apply marketing principles in their own creative projects and how to take advantage of opportunities that exist in the market. The results of this community service show an increase in students' understanding of the basics of marketing and its application in the creative economy. Program participants report that they feel better prepared to apply the knowledge gained in their creative projects and take advantage of opportunities in the creative economy. Therefore, this activity recommends further development and continuity in the implementation of similar programs to strengthen students' knowledge and skills in facing future challenges and opportunities